The ethics of internet-based and other self-help therapies for mental health problems: Still not solved after 50 years - Cuijpers, Pim (Clinical psychology (New York, N.Y.), 2018)
Comments on an article by A. M. Borgueta et al. (see record 2018-09892-001). Borgueta and colleagues convincingly describe in their article how the field of mental health treatment is changing rapidly through the introduction of new technologies and how ethical guidelines have not kept up with the pace of these changes. This is an important issue that should be taken up by the field, and the authors give clear guidelines about what should be done and which subjects deserve priority. The author still do not know whether opponents of this self-help movement were right and we should not have made this television series on the “Coping with Depression” course. These opponents would now certainly also argue that it is not ethical to deliver guided self-help through the Internet outside the regular mental health care system. Personally, author thinks we should inform patients as thoroughly as possible about methods that may be of help to them and that are simple enough to be explained and used by nonprofessionals. Author do not think we should hide this knowledge behind a professional wall, but make it accessible to anyone who may benefit from this type of intervention. Of course, we have to deliver care in a safe way that does not harm patients, but we also have the obligation to help as many people as we can. And if authors can do that by providing them with knowledge about how to apply a treatment to themselves, we should not hesitate to do that. The disease burden of mental disorders is too large for that, both on the personal level of the patient and on the level of our societies. (PsycInfo Database Record (c) 2025 APA, all rights reserved)